(untitled) (Research, Society and Development, 2023)
Introduction: situs inversus is a rare congenital anomaly characterized by the transposition of the abdominal organs, viscera and vasculature, in relation to the sagittal direction, offering an image called “mirror image”. It is classified as total when associated with dextrocardia, while partial situs inversus affects only one or more organs. Objective: to answer what is the evidence about the clinical and anatomical aspects of situs inversus. Methodology: this is an integrative literature review. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases. Information Services Results and Discussion: In situs solitus, the right lung has three lobes and an eparterial bronchus (bronchi above the pulmonary artery), while the left lung has two lobes with a hyarterial bronchus (bronchi below the pulmonary artery), the stomach and the spleen are on the left and the greater lobe of the liver is on the right. The morphological left atrium is to the left of the morphological right atrium. With situs inversus, the left lung has three lobes with an eparterial bronchus and the right lung has two lobes with a hyperarterial bronchus, the stomach and spleen are on the right side of the body, the larger lobe of the liver is on the left, and the morphological left atrium is to the right of the morphological right atrium. Final considerations: it is known that this anatomical asymmetry is established during embryonic formation, specifically, in organ rotation. However, it is worth noting that individuals with total situs inversus alone do not have clinical repercussions, with the exception of cases associated with heart disease. Therefore, almost always, its diagnosis is a finding in imaging tests, such as radiographs, CT scans and ultrasounds.